Developing a Set of Core Outcomes for Trials in Hemodialysis: An International Delphi Survey - Evangelidis, Nicole; Tong, Allison; Manns, Braden; Hemmelgarn, Brenda; Wheeler, David C.; Tugwell, Peter; Crowe, Sally; Harris, Tess; Van Biesen, Wim; Winkelmayer, Wolfgang C.; Sautenet, Benedicte; O’Donoghue, Donal; et al. (American journal of kidney diseases, 2017)
Survival and quality of life for patients on hemodialysis therapy remain poor despite substantial research efforts. Existing trials often report surrogate outcomes that may not be relevant to patients and clinicians. The aim of this project was to generate a consensus-based prioritized list of core outcomes for trials in hemodialysis. In a Delphi survey, participants rated the importance of outcomes using a 9-point Likert scale in round 1 and then re-rated outcomes in rounds 2 and 3 after reviewing other respondents’ scores. For each outcome, the median, mean, and proportion rating as 7 to 9 (critically important) were calculated. 1,181 participants (202 [17%] patients/caregivers, 979 health professionals) from 73 countries completed round 1, with 838 (71%) completing round 3. Outcomes included in the potential core outcome set met the following criteria for both patients/caregivers and health professionals: median score ≥ 8, mean score ≥ 7.5, proportion rating the outcome as critically important ≥ 75%, and median score in the forced ranking question < 10. Patients/caregivers rated 4 outcomes higher than health professionals: ability to travel, dialysis-free time, dialysis adequacy, and washed out after dialysis (mean differences of 0.9, 0.5, 0.3, and 0.2, respectively). Health professionals gave a higher rating for mortality, hospitalization, decrease in blood pressure, vascular access complications, depression, cardiovascular disease, target weight, infection, and potassium (mean differences of 1.0, 1.0, 1.0, 0.9, 0.9, 0.8, 0.7, 0.4, and 0.4, respectively). The Delphi survey was conducted online in English and excludes participants without access to a computer and internet connection. Patients/caregivers gave higher priority to lifestyle-related outcomes than health professionals. The prioritized outcomes for both groups were vascular access problems, dialysis adequacy, fatigue, cardiovascular disease, and mortality. This process will inform a core outcome set that in turn will improve the relevance, efficiency, and comparability of trial evidence to facilitate treatment decisions.